2020
DOI: 10.4103/ijpc.ijpc_157_20
|View full text |Cite
|
Sign up to set email alerts
|

Why i can't breastfeed my new-born baby? Psychosocial dilemma of a COVID-positive post-LSCS mother

Abstract: A 26-year-old postpartum COVID-positive mother admitted in COVID isolation facility at a tertiary care center in India. Her primary physical concern was suture site pain and concerns related to expressed breast milk discarding. Her psychological concerns include distrust on COVID report, belief of unjust isolation, lack of family support, loneliness, feeling of not breast feeding her baby, fear, anxiety, anger, stress, and depression. She was concerned about the stigma anticipated for herself and her baby. Spi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
15

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(31 citation statements)
references
References 8 publications
0
16
0
15
Order By: Relevance
“…COVID-19 and the decreed lockdowns have affected new mother’s mental health. Results of the survey conducted by Hull et al [ 41 ] showed that mothers were experiencing isolation ( n = 31), anxiety or stress ( n = 53), and needing reassurance ( n = 63). As observed in the qualitative reports, mothers’ preoccupations about breastfeeding caused significant anxiety and were related to the belief that breastfeeding could protect their infants against the virus.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…COVID-19 and the decreed lockdowns have affected new mother’s mental health. Results of the survey conducted by Hull et al [ 41 ] showed that mothers were experiencing isolation ( n = 31), anxiety or stress ( n = 53), and needing reassurance ( n = 63). As observed in the qualitative reports, mothers’ preoccupations about breastfeeding caused significant anxiety and were related to the belief that breastfeeding could protect their infants against the virus.…”
Section: Resultsmentioning
confidence: 99%
“…One case report emerged [ 41 ], describing a COVID-19 positive 26-year-old Indian woman in the postpartum period, who gave birth prematurely (at the 28-gestational-week), and whose newborn was in the neonatal intensive care unit (ICU). The mother reported loneliness, distrust regarding the COVID-19 results, belief of unjust isolation, loneliness and lack of family support, fear, anxiety, anger, stress, and depression.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gestantes (n = 403) Índia/ 2020 (35) Apresentar o caso de uma mãe pós-parto COVID positiva de 26 anos, separada de seu bebê prematuro de 28 semanas de gestação, que estava internado na UTIN. Neste caso, o estudo irá destacar as preocupações físicas, psicossociais, espirituais e o estigma que ela teve que enfrentar durante o período de quarentena.…”
Section: Lactantes (N = 29)unclassified
“…influênCia da pandEmia na roTina dE Cuidados ao alEiTamEnTo maTErno Estudos apontaram medidas preventivas adotadas contra a COVID-19 (22)(23)(25)(26)(27)(28)(29)(30)(31)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45) . Destacaram a recomendação do uso de máscara ao amamentar (22)(23)25,28,30,(36)(37)(41)(42)45) , a higienização das mãos antes de tocar no bebê (22,25,28,30,(36)(37)(41)(42) e ao manusear a bomba de leite (22,28,37,(41)(42) e a adoção dos testes para COVID-19 na admissão hospitalar (26,28,30) .…”
Section: Parturientes (N = 42)unclassified